FAKTOR SOSIAL DETERMINAN, POLA MAKAN DAN AKTIFITAS FISIK TERHADAP KEJADIAN OBESITAS PADA ANAK SEKOLAH DASAR KELAS IV DAN V DI KECAMATAN TAMPAN KOTA PEKANBARU - , Yola Humaroh, Dr.rer.nat.dr.BJ.Istiti Kandarina ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Obesity is one of the most serious challenges of public health in the 21 st century. The problem is global and continuously affecting low and middle income countries, especially in urban areas. In 2007 the Province Riau belonged to five provinces with prevalence of obesity in boys of 6-14 years as much as 15.1%. In 2010 the Province Riau belonged to eleven provinces which prevalence of obesity in children of 6-12 years as much as 10.9%. factor of fhysical and social environment such as socio economic, culture/eating habit, unbalanced diet less physical activities have become the major causes of the prevalance of obesity. Objective: To identify associated with the prevalence of obesity in elementary school children at Subdistrict of Tampan Pekanbaru Municipality. Methods: This study was analytic observational intended to identify social factor determinants, eating pattern and physical activity and the prevalence of obesity in elementary school children in Subdistrict Tampan using cross sectional design. It was carried out in April - June 2012, involving 136 samples matching inclusion criteria selected through proportionate random sampling technique. The results of the data collection were analyzed using univariable, bivariable and multivariable techniques. Results: The result of bivariable test showed that there was significant association between social economic factors, such as parentâs education, maternal occupation, size of family, eating pattern and physical activities and the prevalence of obesity (p <0.05). The result multivariable test showed maternal occupation, size of family members, eating pattern and physical activities were factors most dominantly prevalence of obesity (p> 0.05) Conclusions: High socioeconomic families, a pattern of overeating, and mild physical activity were likely to affect obesity in children